Quantum Gods : creation, chaos, and the search for cosmic consciousness - Stenger, Victor J., 1935- (Amherst, NewYork : Prometheus Books, 2009)
Does quantum mechanics show a connection between the human mind and the cosmos? Are our brains tuned into a "cosmic consciousness" that pervades the universe enabling us to make our own reality? Do quantum mechanics and chaos theory provide a place for God to act in the world without violating natural laws? Many popular books make such claims and argue that key developments in twentieth-century physics, such as the uncertainty principle and the butterfly effect, support the notion that God or a universal mind acts upon material reality. The author here examines these contentions in a carefully reasoned analysis of popular theories that seek to link spirituality to physics. Throughout the book, the author alternates his discussions of popular spirituality with a survey of what the findings of twentieth-century physics actually mean. Thus he offers the reader a useful synopsis of contemporary religious ideas as well as basic but sophisticated physics presented in layperson's terms (without equations). Of particular interest in this book is the author's discussion of a new kind of deism, which proposes a God who creates a universe with many possible pathways determined by chance, but otherwise does not interfere with the physical world or the lives of humans.
Belief and nonbelief in America -- What the bleep is the secret? -- Pursuing the Tao -- The guru of GUTs -- Space, time, and matter -- The great paradigm shift -- Deism and Darwinism -- The spooky quantum -- The elements of matter -- Chaos, complexity, and emergence -- Return to reduction -- Ghost busting the quantum -- Quantum philosophy -- Where can God act? -- The God who plays dice -- Nothingism.
Includes bibliographical references (p. 265-275) and index(p.277-289)
Keywords: Quantum theory -- Religious aspects; Consciousness -- Religious aspects